Comparison of the alveographic qualification and the baking quality of winter wheat - Tóth, Árpád; Sipos, Péter; Borbély, Mária; Győri, Zoltán (Acta Agraria Debreceniensis, 2007)
On the basis of the operative French regulations, we qualified the alveographic qualification and the valorigraphic qualification respectively for each of the 10-14 winter wheat varieties grown each year between 2002-2005, and used in a field experiment at the Karcag Research Institute of the University of Debrecen. The field experiment at the Látókép Research Institute of the University of Debrecen allowed us to examine the alveographic and valorigraphic values of the samples of GK Öthalom and Fatima 2 winter wheat varieties taken from an 8 year period (1997-1999 and 2001-2005).Throughout the experiments on samples from the Karcag Research Institute and Látókép Research Institute of the University of Debrecen, we tried to find whether the alveographic W value or the P/L value provides the safer method for the qualification of wheat samples, instead of the qualification commonly used in Hungary. We found that in terms of the samples from the Karcag Research Institute, the baking quality and the W value in each of the examined years, while in terms of the Látókép Research Institute, most of the years showed a close positive correlation, contrary to the close negative relationship between the baking quality and the P/L value. The correlation index varied depending on the year, the variety, and fertilizer doses, which require further examinations.